Path planning for autonomous ground vehicles based on quintic trigonometric Bézier curve: Path planning based on quintic trigonometric Bézier curve - Bulut, Vahide (Journal of the Brazilian Society of Mechanical Sciences and Engineering, 2021)
Path planning is one of the essential steps for autonomous ground vehicles or even wheeled mobile robots. This paper proposes a general framework for the path planning using quintic trigonometric Bézier curve with two shape parameters and C 3 continuity. We express that when there are obstacles, predefined path can be adjusted by only using shape parameters without altering any obstacle. Additionally, the velocity, lateral acceleration, longitudinal and lateral jerks of the predefined cubic and quintic Bézier, and cubic and quintic trigonometric Bézier paths are compared. Also, a path surface for autonomous ground vehicles can be generated using developable surfaces.